Retromalisus damzeni, gen. et sp. nov., a second Baltic amber taxon of the extinct family Berendtimiridae (Insecta: Coleoptera). Issue 17 (2nd May 2020) - Kazantsev, Sergey
ABSTRACT: A second Baltic amber taxon, Retromalisus damzeni, gen. et sp. nov., is discovered in the previously monotypic extinct family Berendtimiridae. The morphological portrait of Berendtimiridae is complemented with the data on the structure of prosternum and abdomen.